A Russian Tragedy. - Grier, David Alan (Computer (00189162), 2017)
Despite its success, there seems to be a gap between the Russian software industry and its Western counterparts. The web extra at https://youtu.be/QpLvVw0Z4rM is an audio recording of author David Alan Grier reading his Global Code column, in which he discusses Russian software industry.